A novel monitor for practical brain-computer interface applications based on visual evoked potential. Issue 1 (3rd April 2021) - Maymandi, Hamidreza; Perez Benitez, Jorge Luis; Gallegos-Funes, F.; Perez Benitez, J. A.
ABSTRACT: This study proposes and evaluates a novel monitor for generating visual-evoked potential (VEP) for daily use brain–computer interface (BCI) applications. The backlight of a conventional monitor was replaced with a matrix panel of LEDs to take maximum advantage of both the computer monitor and LED in generating VEP. This matrix contains 32 cells working independently at an adjustable range of flickering frequencies. The software was further developed to control the number of cells as needed. Thanks to this design, the monitor can work simultaneously as a conventional monitor and as a high-frequency visual stimulator. In total, this monitor provides up to 32 targets at all ranges of frequencies. The proposed monitor exhibits high performance in generating stable high-frequency VEP(34Hz-49.5Hz). This feature allows the monitor to cope with the main deficiencies of BCI devices such as the low number of targets, low-frequency stimulation, and lack of implementing an integrated system.